Response of laying hens to methionine plus cystine intake by dilution technique - Palma Bendezu, Hilda Cristina [UNESP]; Sakomura, Nilva Kazue [UNESP]; Hauschild, Luciano [UNESP]; Silva, Edney Pereira da [UNESP]; Paula Dorigam, Juliano Cesar de [UNESP]; Malheiros, Euclides Braga [UNESP]; Kochenborger Fernandes, Joao Batista [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2015)
The objective of this study was to measure the response of Dekalb White laying hens to different intakes of digestible methionine + cystine (met+cys) to optimise their performance. Two hundred eighty-eight Dekalb White laying hens, ranging in age from 33 to 48 weeks, were used in the study. The birds were randomly allocated into eight treatment (levels of met+cys and the control treatment) groups with six replicates of six hens per unit. The experimental diets consisted of seven increasing levels of met+cys (1.37, 2.75, 4.14, 5.51, 6.89, 7.92 and 8.95 g kg(-1)) and were prepared using a dilution technique. A control treatment was used to confirm that the limiting response was due to met+cys intake. Egg production, feed intake, egg weight, egg mass and feed conversion per mass were measured. The data were analysed with repeated measures and regression analyses using Broken Line and Quadratic models, as well as using the combination of both models. The different met+cys intakes influenced the studied variables; all the variables except feed conversion per mass were significantly different between the periods and levels. The digestible met+cys intakes based on the association of the Broken Line and Quadratic models to optimise the birds'response to egg mass are 671 mg/bird d for 33 to 36 weeks, 728 mg/bird d for 37 to 40 weeks, 743 mg/bird d for 41 to 44 weeks, and 770 mg/bird d for 45 to 48 weeks.
Keywords: Broken Line; Dose-response; Models; Requirement; Statistic